2020
DOI: 10.24219/rpi.v4i1.1476
|View full text |Cite
|
Sign up to set email alerts
|

ANTA BRASILEIRA – <em>Tapirus terrestris</em>: características gerais, mitológicas e seu conhecimento popular nas regiões do Noroeste e do Alto Paranaíba em Minas Gerais

Abstract: <p>Objetivou-se fazer um levantamento sobre a anta (<em>Tapirus terrestris </em>- Linneaus - 1758), descrevendo suas características gerais e sua mitologia, além de buscar, através de entrevistas, o conhecimento das pessoas acerca desta espécie com vistas à sua conservação e bioética. O conhecimento agregado sobre as características gerais e a mitologia de animais silvestres pode colaborar para sua conservação, bem como para resguardar seus direitos para a educação ambiental. A metodologia ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Interviewees in our study area had a positive perception of lowland tapirs, a similar result to the one found in the Caatinga biome, where there were no reports of negative situations associated with the tapir (Borges et al, 2020). This positive perception represents the acceptance of lowland tapirs in the region, a meaningful result for the conservation of this vulnerable species, especially since positive attitudes towards a species and low risk perception associated with it are key predictors of tolerance and favorable human responses towards wildlife (Jacobs et al, 2012;Bathia et al, 2019).…”
Section: Perceptions and Poaching Of The Lowland Tapirsupporting
confidence: 84%
See 1 more Smart Citation
“…Interviewees in our study area had a positive perception of lowland tapirs, a similar result to the one found in the Caatinga biome, where there were no reports of negative situations associated with the tapir (Borges et al, 2020). This positive perception represents the acceptance of lowland tapirs in the region, a meaningful result for the conservation of this vulnerable species, especially since positive attitudes towards a species and low risk perception associated with it are key predictors of tolerance and favorable human responses towards wildlife (Jacobs et al, 2012;Bathia et al, 2019).…”
Section: Perceptions and Poaching Of The Lowland Tapirsupporting
confidence: 84%
“…According to our results, conflict did not appear as a reason for lowland tapir poaching, given that the impact of tapirs on crops was not perceived as detrimental by most interviewees, and there was no report of tapir retaliatory killing in the region. Borges et al (2020) also had similar findings regarding the absence of conflicts with lowland tapir in the Cerrado biome while Pianca and Monteiro (2005) reported that conflicts with lowland tapirs were a relevant issue in the Atlantic Forest. Although lowland tapirs appeared as the third most-cited species to cause conflict in our study area, we believe this result reflects the fact that all interviewees were questioned specifically about the lowland tapir, the focus of the study.…”
Section: Patterns In Human-wildlife Conflictmentioning
confidence: 54%